Maize price seasonality in Ethiopia: Does access to improved grain storage technology matter for farmers’ welfare? - Negede, Betelhem M.; Voors, Maarten; De Groote, Hugo; Minten, Bart (International Association of Agricultural Economists, 2021)
African seasonal price variability for cereals is two to three times higher than price variability on the international reference market. Seasonality is even more pronounced when access to storage is limited, leading to low opportunities for price arbitrage. This leads to low incomes and food insecurity for smallholder farmers during the lean season, the “higher price” season. One solution to reduce seasonal stress is the use of improved storage technologies. Using data from a randomized controlled trial, we study the impact of hermetic bags, a technology that protects stored maize grain against insect pests, and helps to store it longer, in a major maizegrowing region of Western Ethiopia. We find considerable price seasonality: maize prices in the lean season are up to 36% higher than maize prices after harvesting. However, we find no evidence that hermetic bags improve welfare, except that these bags allowed for a marginally longer storage period of maize intended for sale. This “near-null” effect is due to the fact that maize storage losses in our study region are not as high as previous studies suggested, but just under 2% of annual storage. To safely store maize, farmers have benefited from the recent advance in access to a cheap but toxic alternative fumigant. Looking at heterogeneity treatment effects, we find that farmers who are cash constrained store 4% less than those who are not. This behavior generates a large scale price seasonality that further lowers farmers’ welfare.